Periodontal Probing of Dental Furcations Compared With Diagnosis by Low‐Dose Computed Tomography: A Case Series. Issue 12 (1st December 2013) - Laky, Markus; Majdalani, Shaila; Kapferer, Ines; Frantal, Sophie; Gahleitner, André; Moritz, Andreas; Ulm, Christian
Abstract : Background: Therapeutic decisions in periodontal surgery are based on the accurate diagnosis of the furcation. Clinical probing is the basic diagnostic tool; however, the accuracy of clinical probing to distinguish Class II and Class III furcation defects is unknown. Therefore, this study compares clinical probing diagnoses to those of computed tomography (CT). Methods: Seventy‐five patients with severe periodontal disease were enrolled in this case series study. A total of 582 furcation sites in molars were assigned for the diagnosis of Class II and Class III furcation defects by clinical probing. Diagnosis based on CT served as a reference. Results: The degree of furcation involvement on clinical findings was confirmed in 57% of the sites, whereas 20% were overestimated and 23% were underestimated compared with the radiologic analysis. Only 32% of Class III furcations in the CT scan were detected clinically. The best correlation of CT scan and clinical probing was found at buccal furcation sites in the mandible, with a κ‐coefficient of 0.52, and buccal furcation sites in the maxilla, κ = 0.38. The κ‐coefficient was 0.35 for lingual furcations, 0.29 for mesial furcations, and 0.27 for distal furcations, showing weaker correlations. Conclusions: CT scans offer more detailed information on furcation involvement than clinical probing. Especially before surgical treatment, three‐dimensional radiographic imaging can be a useful tool to assess the degree of furcation involvement and optimize treatment decisions.